Cesium-oleate passivation for stable provskite photovoltaics - Guo, Xintong (2020)
Despite their emergence as promising materials for low-cost and efficient energy power generation technology, hybrid organ-ic-inorganic lead-halide perovskites’ instability towards moisture and heat stress remains a serious obstacle that needs to be tackled for commercialization. Here, we show improved moisture and thermal stability through the use of cesium oleate to modify the perovskite/hole transporting material (HTM) interface. Passivation using cesium oleate does not induce the for-mation of any low dimensional perovskites, suggesting that the organic species only passivates the perovskite’s surface and grain boundaries. As a result, enhanced hydrophobic character of perovskite film is realized upon passivation, evidenced by high water contact angle of 107.4 degree and improved stability at ambient condition (relative humidity of ~70%, room tem-perature). Concomitantly, the proposed passivation strategy leads to increased amount of cesium concentration within the films, resulting in beneficial enhanced thermal stability of the film at 85oC. By maintaining the three-dimensional (3D) structure of the solar absorber while concurrently passivating the interfacial defects and vacancies, improved open-circuit voltage (Voc) and unsacrificed short-circuit current density (Jsc) were obtained from the treated devices, leading to power conversion effi-ciencies of over 18%. When stored in a humid environment (relative humidity of ~55%), devices with cesium oleate passivation maintain 88% of its initial PCEs after 720 hours, degrading two times slower than those of the control. This work offers a strat-egy of coating 3D perovskites with unique combination of inorganic cation and long chain organics to provide hydrophobicity and moisture stability to the solar absorber layer, while maintaining good device performances.